The effectiveness of National Single Window in facilitating Malaysian trade - a study in Klang Valley / Nor Bakhriah Sarbani - Sarbani, Nor Bakhriah (2014)
The single window concept was recommended by the United Nations European Economic Commission (UNECE) to support the trade facilitation initiative to overcome a major nontariff barrier associated with the international cross-border activities, especially relating to the information and data issue. Every cross-border physical cargo movement is entwined with information that carries the status of the cargo. Information and data management during the cross-border activities plays a vital role which contributes to the efficiency of supply chain and public administration that indirectly has an impact on market performance. In conjunction with the international demand, Malaysia has developed its National Single Window (NSW) as part of the country's national agenda to facilitate international trade. NSW is also a prerequisite to regional integration through the ASEAN Single Window (ASW) development in the ASEAN Economic Community (AEC) to support the free flow of goods among the member countries. Single window remains a major issue among the respective community in Malaysia. In the event of ASW protocol and AEC agenda, the implementation of the single window concept is far from its aim to become a single focal point for the cross-border custom clearance process. Currently, single window is not a purely single focus point where virtually it is a version of single window front-end but with the existence of multiple windows in the back-end due to the redundant control of the respective authorities on top of custom approval. This research will answer three main objectives: first, to determine the structure of current single window implementation in Malaysia within the trade facilitation initiatives in Klang Valley; second, to identify in depth the contributing factors for effective single window in facilitating trade process; and finally, to propose recommendations to improve the present practice of National Single Window (NSW) in Klang Valley, Malaysia. This study has adopted a qualitative research approach. In-depth face-to-face semistructured interviews were conducted with 21 participants from various stakeholders category in single window community. The participants were selected using purposive sampling. Every participant was asked a standard set of controlled questions. All interviews were properly recorded, coded, and analyzed using thematic analysis. Results of the interviews were triangulated with the focus group discussions in the validation process. The findings of this study were highlighted in a set of eight factors, namely policy establishment, institutional support, stakeholders' awareness, electronic system reliability, training, ICT supporting facility, simplified procedures, and steering committee commitment.